HUBUNGAN KARAKTERISTIK DAN LINGKUNGAN FISIK RUMAH DENGAN KELUHAN KESEHATAN MATA PENGRAJIN ULOS DI KELURAHAN KEBUN SAYUR KECAMATAN SIANTAR TIMUR KOTAMADYA PEMATANGSIANTAR TAHUN 2012 - Sri Lestari; evi Naria; surya dharma (Lingkungan dan Kesehatan Kerja, 2013)
Relationship of characteristics and physical environment of houses with the eye complaints of those ulos craftsmen at Kelurahan Kebun Sayur Kecamatan Siantar Timur Kotamadya Pematangsiantar in 2012. Eye complaint is caused by using the sense of vision during working that usually accompanied by a uncomfortable vision. The purpose of this study to determine the relationship of characteristics and physical environment of houses with the eye complaints of those ulos craftsmen at Kelurahan Kebun Sayur Kecamatan Siantar Timur Kotamadya Pematangsiantar in 2012. The method used in this study was an analytic survey with cross sectional design. The sample was total from all populations. The result of research showed that 68,2% of respondents in age was not susceptible, 54,5% had myopia, 72,7% was layout tool work, 65,9% was to see objects 25-30 cm, 59,1% was working long time > 8 hours/day, 61,4% had working period > 3 years, 86,4% workspace lighting was not eligible, 72,7% workspace ventilation was not eligible, and 79,5% its workspace temperature was eligible. The result of statistics test with Chi-square obtained that age and distance to see object had no significant association with the complaint of eyes while the refractive eye abnormalities, working long time, and working period had significant association. The result of statistics test with Fisher Exact was obtained that the layout tool work and room temperature had no significant association with the eyes complaint while lighting and space ventilation have a significant association with the complaint of eyes. For the craftsmen who live in Kelurahan Kebun Sayur should keep residential health environment especially on lighting and space ventilation to weave ulos. Keywords : characteristics, phsycal house environment and eye complaint